Effect of Material Changes on the Total Harmonic Distortions Caused by Aluminum Electrolytic Capacitors - Rene Kalbitz (IEEE Access)
This paper describes a comparative study of the total harmonic distortion (THD) caused by commercial electrolytic capacitors. The study includes selected capacitors with a capacitance of $470~μ \text{F}$ that are commercially available from eiSos Würth Elektronik, as well as custom-made capacitors that are manufactured at the production site. For the custom-made samples, the water content of the electrolyte, as well as the paper density, was systematically varied. The discussion of audibility of distortion is based on human sound perception. The results are compared with model calculations to check the plausibility of the measured harmonic distortions. This study concludes that capacitors do not introduce significant distortions at fundamental frequencies when transmitting signals. Modifications of the electrolyte or the separator paper practically do not influence the THD.